ELEMEN PENTING PENDORONG KINERJA UMKM PADA SEKTOR FASHION DI KOTA DENPASAR - Indrayana, I Putu Dony; Eka Idayanti, I Dewa Agung Ayu; Kertiriasih, Ni Nengah Rupadi (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2025)
This research is based on the existence of a research gap and differences in focus regarding entrepreneurial orientation, capabilities, and entrepreneurial knowledge on the performance of SMEs. Additionally, this study aims to address the issue of declining performance among SMEs in the fashion sector in Denpasar City. The research was conducted on SMEs in the fashion sector in Denpasar City, with a total population of 7,896 SMEs. The sample size was calculated using Slovin's formula, resulting in a sample of 100 SMEs in the fashion sector. All data obtained from the distribution of questionnaires were deemed valid and were subsequently analyzed using SPSS 25. The results indicate that entrepreneurial orientation, capabilities, and entrepreneurial knowledge each have a positive and significant effect on the performance of SMEs. Furthermore, these three variables collectively have a positive and significant impact on SME performance. The implications of this research suggest that enhancing entrepreneurial orientation can be achieved by focusing on innovation indicators. Capabilities can be improved by paying attention to distribution networks, and entrepreneurial knowledge can be enhanced by considering knowledge management indicators. Overall, the performance of SMEs can be increased by concentrating on their profit-generating capabilities. Keywords: Entrepreneurial Orientation, Capabilities, Entrepreneurial Knowledge, SME Performance, Fashion Sector